Pemanfaatan Aplikasi SIPEBI untuk Pemelajar BIPA - Syihaabul Hudaa (Jurnal Bahasa Indonesia bagi Penutur Asing, 2021)
Learning Indonesian for foreign speakers is not an easy thing. This difficulty arises because in Indonesian there are various kinds of language rules regulated by: KBBI, PUPI, PUEBI, and other grammars. The purpose of writing this article is to convey that the use of technology can streamline learning activities. This paper will discuss how the Sipebi application can be used for BIPA learning activities, especially in studying writing competence. This article is still limited to a literature review, so this design still needs to be implemented in learning activities. However, the use of the Sipebi application in improving the ability of BIPA students in writing was considered effective based on the design presented by the researcher. The design includes: application introduction, installation, application utilization, writing, and evaluation. By utilizing the Sipebi application, researchers hope that BIPA students will be happier learning Indonesian.